التداولية مصطلحا ومفهوما فِي الدراسات العربية المعاصِرَة عَتبات أَوليةٌ - جرادي, يعرب (University of Eloued جامعة الوادي, 2017)
قُمنَا في هذا المقال؛ بتوضيح أهمّ المحطَّات العربيَّة المُقاربة للتَّداولِيَّة؛ بوصفِها منهجًا أو تيَّارًا بحثِيًّا جَدِيدًا على الدراسات اللّسانية العربية، وذلك بتَتَبُّعِ المُصطلح والمفهومِ الدَّال علَيِهما في أعمال الباحثين العرب الذين اشتَغلوا على هذا الموضوع، ابتداء بــ: طه عبد الرحمن الذي وضع المصطلح؛ ونظر له من النَّاحية الفلسفية واللسانية والنقدية، ثم المُتوكل الذي اشتغل على جوانبه الوظيفية، ثم مسعود صحراوي الذي وقف على التَّقارب الموجود بين أفعال الكلام والإنشاء، فمحمد يونس الذي درس مناهج الأصوليين؛ ونماذجهم التَّخاطُبِيَّة المُقارِبة للنَّص، فعَبد الرحمن الحاج صالح الذي أَعاد قراءة ما اشتغل عليه لِسَانيَّا؛ هذه المرة في نظرية الوضع والاستعمال؛ بالترَّكيز عَلى الخِطاب والتَّخاطب، وُصولا إلى العُمري الذي التقى مع التداولية عندما عمل على قراءة البلاغة العربية من منظور البلاغة الجديدة، ختاما برشيد يحياوي الذي عمل على بلاغةٍ جديدةٍ للكلام لا اللغة؛ بإعمال نظرية التواصل، وقد قدمنا ذلك بتحرير أهم النقاط التي اجتمعوا عليها، وتلك التي افترقوا فيها. We have clarified in this article, the most important events ;of the Arab approach to Pragmatics; as a method or a new research stream in Arabic linguistics studies, and it keeps track of the term and the concept signifier them in the work of Arab researchers who worked on this subject, starting with: Taha Abdel-Rahman, who put the term; considered him from the philosophical and linguistic and critic, then El Moutawakel, who worked on the functional aspects, then a Massoud Sahrawi, who studied on the convergence that exists between the acts of speech and Elenchaa, to Mohammad M Younis, who has studied methods of Fundamentalists; and their Pragmatics models approach; to the text, Abdel-Rahman al-Haj Saleh, who re-read what worked him in linguistic; this time in the situation and use theory; focusing on speech and pragmatics, all the way to Alomary, who met with the pragmatics when he worked on reading Arabic rhetoric from the perspective of the new rhetoric, Finally Racheed Yahyaoui, who worked on a new rhetoric for parole; not for language;by the realization of communication theory, finally we clear up the most important points; that met them, and those that separated them.
Keywords: التداولية، الدراسات العربية، البلاغة; pragmatics, Arabic Studies, Rhetoric